Trauma and psychotic experiences: transnational data from the World Mental Health Survey. (December 2017) - McGrath, John J.; Saha, Sukanta; Lim, Carmen C. W.; Aguilar-Gaxiola, Sergio; Alonso, Jordi; Andrade, Laura H.; Bromet, Evelyn J.; Bruffaerts, Ronny; Caldas de Almeida, José M.; Cardoso, Graça; de Girolamo, Giovanni; Fayyad, John; et al.
Abstract : Background: Traumatic events are associated with increased risk of psychotic experiences, but it is unclear whether this association is explained by mental disorders prior to psychotic experience onset. Aims: To investigate the associations between traumatic events and subsequent psychotic experience onset after adjusting for post-traumatic stress disorder and other mental disorders. Method: We assessed 29 traumatic event types and psychotic experiences from the World Mental Health surveys and examined the associations of traumatic events with subsequent psychotic experience onset with and without adjustments for mental disorders. Results: Respondents with any traumatic events had three times the odds of other respondents of subsequently developing psychotic experiences (OR=3.1, 95% CI 2.7–3.7), with variability in strength of association across traumatic event types. These associations persisted after adjustment for mental disorders. Conclusions: Exposure to traumatic events predicts subsequent onset of psychotic experiences even after adjusting for comorbid mental disorders.